Brain rules : 12 Principles for Surviving and Thriving at Work, Home, and School - Medina, John J. (Pear Press, 2008)
Most of us have no idea what's really going on inside our heads. Yet brain scientists have uncovered details every business leader, parent, and teacher should know--such as the brain's need for physical activity to work at its best. How do we learn? What exactly do sleep and stress do to our brains? Why is multi-tasking a myth? Why is it so easy to forget--and so important to repeat new information? Is it true that men and women have different brains? In Brain Rules, molecular biologist Dr. John Medina shares his lifelong interest in how the brain sciences might influence the way we teach our children and the way we work. In each chapter, he describes a brain rule--what scientists know for sure about how our brains work--and then offers transformative ideas for our daily lives. Medina's fascinating stories and sense of humor breathe life into brain science. You'll learn why Michael Jordan was no good at baseball. You'll peer over a surgeon's shoulder as he finds, to his surprise, that we have a Jennifer Aniston neuron. You'll meet a boy who has an amazing memory for music but can't tie his own shoes.